Meeting of the Religions: A Reappraisal of the Christian Vision - Thomas , R C (Journal of Dharma, 1983)
V. Cyriac Meeting of the Religions: A Reappraisal of the Christian Vision Madras-Madurai : Dialogue Series, 1982, xix +214 pp. Price Rs. 30.00, 6.00.